Green Hydrogen Separation from Nitrogen by Mixed‐Matrix Membranes Consisting of Nanosized Sodalite Crystals. Issue 19 (22nd January 2019) - Yang, Ge; Guo, Hailing; Kang, Zixi; Zhao, Lei; Feng, Shou; Jiao, Feng; Mintova, Svetlana
Abstract: Nanosized sodalite (Nano‐SOD) crystals were used as active filler to prepare mixed‐matrix membranes (MMMs) for promoting the H2 /N2 gas‐separation performance. The Nano‐SOD crystals with extremely small crystallites (40–50 nm) were synthesized from a colloidal suspension free of organic structural directing agent and uniformly dispersed in the polyetherimide (PEI) matrix. The Nano‐SOD filler with a suitable aperture size (2.8 Å) allowed only H2 molecules to pass through and rejected the N2, thus improving the selectivity of the membranes. The high dispersion of Nano‐SOD crystals in the polymer matrix and the interactions between the inorganic and organic phases greatly improved the membrane separation performance and minimized interfacial holes. The MMMs showed a high H2 permeability (≈7155.1 Barrer at 25 °C under atmospheric pressure) and an ideal H2 /N2 selectivity factor of approximately 16.9 in a single gas test. Moreover, in a gas mixture (H2 /N2, 25–100 °C), the selectivity factor increased significantly to approximately 30.9. The high stability of the MMMs, which consist of highly dispersed Nano‐SOD crystals in a PEI matrix for H2 /N2 separation (6 weeks continuous test), makes them an important material for ammonia synthesis applications that require and also release a large amount of H2 . Abstract : Into the Matrix : Mixed‐matrix membranes with uniformly dispersed nanosized sodalite crystals in a polymeric matrix are prepared. The sodalite nanocrystals are synthesized free of organic template with large external surface area and monomodal particle‐size distribution. The sodalite nanocrystals with a suitable aperture size of the cages (2.8 Å) allow only H2 to penetrate whereas N2 is rejected. The mixed‐matrix membranes show high H2 flux and selectivity and will be of great importance for synthetic ammonia processing, which demands and releases a large amount of H2 .